Abundance of sclerobionts and presence of malformation on Middle Devonian brachiopods from Skały, Poland (Dobruchna Member, Skały Formation) - Anna Brychcy; Michał Zatoń; Rafał Nawrot; Adam T Halamski; Michał Rakociński (PANGAEA, 2023)
Brachiopod shells were collected from a large heap adjacent to the Semav Stones Skała Quarry in Skały (Holy Cross Mountains, Poland) in order to describe sclerobiont diversity, abundance and colonization patterns. All specimens derive from the Dobruchna Brachiopod Shale Member of the shaly-calcareous Skały Formation (ensensis conodont Zone, Eifelian). Both articulated shells and isolated valves were sampled, but fragmentary specimens were excluded. Each brachiopod specimens (separately dorsal and ventral valves) was inspected under a binocular microscope for the presence of sclerobionts and shell malformations. Each sclerobiont was determined to the lowest possible taxonomic level and counted. Well-separated colonies of clonal epibionts were treated as separate specimens. Only brachiopod specimens with at least one sclerobiont or malformation are included in the dataset.